1990
DOI: 10.1289/ehp.9086229
|View full text |Cite
|
Sign up to set email alerts
|

Influence of food-environment interactions on health in the twenty-first century.

Abstract: The quality and safety of foods are affected by the environment, and the quality and safety of the environment are, in turn, affected by foods and food processing. To explore these interrelationships, as they might exist in the twenty-first century, one must speculate regarding future changes in foods and food processing.Several trends in food processing seem likely to predominate into the twenty-first century, and they will be, for the most part, evolutionary in nature and of low consumer visibility. These tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Issues such as animal health, human health, the sustainability of animal agriculture, and the role of regulatory and public health agencies have dominated the agenda over the years (Ravenel et al, 1926;White, 1964;Lake, 1970;Roberts, 1970) and continue to be relevant today (Fennema, 1990;Bryan, 2001;Oliver et al, 2005). More recently, epidemiology, farm biosecurity, food safety, and environmental protection dominate an increased proportion of our research and policy focus.…”
Section: Introductionmentioning
confidence: 99%
“…Issues such as animal health, human health, the sustainability of animal agriculture, and the role of regulatory and public health agencies have dominated the agenda over the years (Ravenel et al, 1926;White, 1964;Lake, 1970;Roberts, 1970) and continue to be relevant today (Fennema, 1990;Bryan, 2001;Oliver et al, 2005). More recently, epidemiology, farm biosecurity, food safety, and environmental protection dominate an increased proportion of our research and policy focus.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the interaction of the environment with conventional food production, the summing up suggested that "the quality of the environment influences the quality and safety of foods and an unhealthful environment can render food unwholesome" (4). A review on risk management frameworks for human health and environmental risks (5) has also focused on guidelines for assessing human health risks from environmental hazards and stresses "the role and relationship between risk assessment and risk management" as well as the principle of "consulting with the community to identify their concerns".…”
Section: Introductionmentioning
confidence: 99%